Analgesic, Anti-inflammatory, Anti-ulcerogenic Effects, and Acute Toxicity of Tacca integrifolia Extract - Thatree Autsavakitipong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Plants of Taccaceae family are used as a folk medicine for the relief of pain, fever, incised wounds and gastric ulcers. In Thailand, rhizomes of Tacca integrifolia are used for controlling blood pressure, improving sexual function; whole plant and leaves are used for urticaria, tumor, and as food. The analgesic, anti-inflammatory, and anti-ulcerogenic activities of T. integrifolia are interesting activities that still lack of scientific data. This study was performed to investigate the effects and the possible mechanism of action of ethyl acetate extract of leaf of T. integrifoli (TI extract) in animal models by using writhing response in mice and tail flick-test in rats models to test analgesic activity. Ethyl phenyl propiolate (EPP)-induced ear edema, carrageenan- and arachidonic acid-induced hind paw edema, and cotton pellet-induced granuloma formation in rats models were used to examine anti-inflammatory activity. Anti-gastroulcerogenic activity was evaluated by using EtOH/HCl-, indomethacin-, and restraint water immersion stress-induced gastric lesions in rats. Pylorus ligation and gastric visible mucus secretion models were used to examine the mechanism of anti-gastroulcerogenic activity. Additionally, acute oral toxicity of TI extract was also investigated. The results suggest that TI extract at oral doses of 50 to 200 mg/kg showed analgesic effect on acetic acid-induced writhing response in mice and its mechanism may be via peripherally pathway because it had no effect on the tail-flick test in rats. TI extract (3 mg/ear) significantly reduced the edema formation on EPP-induced ear edema, and at oral doses of 50 to 200 mg/kg, TI extract showed the inhibitory effect on the edema formation of the rat paw induced by carrageenan and arachidonic acid. TI extract possessed anti-inflammatory activity in acute inflammation and the possible mechanism is suggested via the inhibition of cyclooxygenase (COX) and lipooxygenase (LOX) pathways. TI extract had no effect on cotton pellet-induced granuloma formation in rats model. TI extract showed anti-gastroulcerogenic effect on EtOH/HCl- and indomethacin-induced gastric ulcer in rats without effect on restraint water immersion stress-induced gastric lesions model. The mechanism of anti-gastroulcerogenic effect may involve the preservation and/or synthesis of the gastric mucus but was not involved the inhibition of gastric acid secretion. Additionally, TI extract at an oral dose of 2,000 mg/kg did not cause acute toxicity in female rats. In conclusion, the ethyl acetate extract of T. integrifolia leaves possesses analgesic, anti-inflammatory, and anti-gastroulcerogenic effects. The results support the use of T. integrifolia as traditional medicine and may lead to develop the major active components to be used for analgesic, anti-inflammatory, prevention and/or treatment of gastric ulcer in the future.